Developing Sustainable Livelihood Potential as a Strategic Step to Improve Economic Welfare Through the Utilization of Vacant Land in Jingah Village - Saputri, Tamara Aulia Sari; Cahyati , Berlian Dwie; Lestari , Shifa Soraya; Hasanah, Uswathun; Yusril, Yusril; Alrizki , Muhammad Akhmal; Olo , Tarno Bendre; Maulana , Anas (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
This study aims to develop sustainable livelihood potential in Jingah Village through the utilization of unused vacant land. Through the Community Service Program (KKN) conducted by IAIN Palangka Raya students, the village community was provided with training on vegetable cultivation. The vacant land in the village has not been utilized optimally due to a lack of knowledge and limited economic conditions. With this training, it is expected that the community can enhance their income and food security through vegetable planting. The methods used in this research include observation, extension services, organic fertilizer production practices, and mentoring until harvest time. The research findings indicate that proper plant care, including regular watering and the application of manure, significantly affects harvest success. Seedling planting is carried out collectively using suitable growing media, such as eggplant, tomatoes, and chili peppers. These findings suggest a significant potential to improve the local economy and the welfare of the community through empowerment based on vegetable cultivation techniques.